Community-based interventions to increase dairy intake in healthy populations: a systematic review - Zeinab Nikniaz; Jafar Sadegh Tabrizi; Morteza Ghojazadeh; Mahdieh Abbasalizad Farhangi; Mohammad-Salar Hosseini; Motahareh Allameh; Soheila Norouzi; Leila Nikniaz (Frontiers Media S.A., 2020)
Abstract Background Considering the low frequency of dairy intake in the population, interventions aiming to increase its consumption can be a priority for any health system. Objective This study aims to summarize community-based interventions for improving dairy consumption and their effectiveness to help policy-makers in designing coherent public health strategies. Methods This study was conducted in 2019, using PubMed/MEDLINE, Scopus, EMBASE, Cochrane Library, Web of Science, ProQuest, and Google Scholar. Two independent reviewers selected the eligible studies, and the outcomes of interest were extracted. The quality of eligible studies was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for randomized controlled trials and quasi-experimental studies. Results Out of 521 initially identified articles, 25 studies were included. Interventions reported in 19 studies were effective in increasing dairy consumption. Interventions in high-income countries were more effective than those in middle- and low-income countries. Interventions in health centers and supermarkets were more effective than the community and school-level interventions. Interventions in supermarkets and adolescents as target groups were more effective than children, middle-aged people, and the elderly. Also, educational interventions and changing buying/selling pattern were more effective than multiple interventions. Interventions longer than 24 and 48 weeks were more effective than shorter interventions. Conclusion Three policy options including educational interventions, multiple interventions, and changing the purchase pattern are suggested. It seems that applying all of the interventions together can be more effective. Also, long-term and well-designed future studies in different settings are recommended to confirm these results.